2019
DOI: 10.7759/cureus.5050
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity Indicators with Hypertension in Type 2 Diabetes Mellitus Patients

Abstract: Objectives: To study the association of waist circumference (WC), waist to hip ratio (WHR) and body mass index (BMI) with hypertension in type 2 diabetes mellitus (DM) patients in a tertiary care hospital. Methods: The anthropometric measures of patients were recorded in the Diabetic Outdoor of Nishtar Hospital Multan from 2013 to 2018 after taking approval from the Institutional Ethical Review Committee. All patients were evaluated in detail after obtaining informed consent. Data was entered and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Our participants showed elevated BP, BG, and BMI. Such a clinical profile resonates with previous diabetes studies [ 47 ]. Due to the nature of metabolic disease, factors such as high BP, diabetes, and obesity are shown to be the most suitable therapy areas to address via digital health.…”
Section: Discussionsupporting
confidence: 87%
“…Our participants showed elevated BP, BG, and BMI. Such a clinical profile resonates with previous diabetes studies [ 47 ]. Due to the nature of metabolic disease, factors such as high BP, diabetes, and obesity are shown to be the most suitable therapy areas to address via digital health.…”
Section: Discussionsupporting
confidence: 87%
“…Existing evidence suggests that WHR is a predictor of T2DM, 83 and T2DM patients with a high WHR were more likely to be hypertensive as compared to those with normal WHR. 84 Recent studies demonstrated that GDF-15 is a key regulator of body weight in animals, mainly through suppression of food intake and is also linked to inflammation, 24 , 28 , 85 cardiovascular disease, 86 and metabolic and mental disorders. 27 , 29 , 30 These and other studies suggest the protective role of GDF-15 in various disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to analyze the relationship between various anthropometric indices and HDC. Hypertension and diabetes are closely related to each other and often coexist [ 2 , 12 , 13 , 15 – 20 , 63 , 64 ]. Several studies have noted that hypertension is the most common complication of diabetes [ 2 , 12 18 ].…”
Section: Discussionmentioning
confidence: 99%